(untitled) (Experimental biology, 2025)
The article discusses biochemical changes occurring in cattle after vaccination against foot-and-mouth disease. Particular attention was paid to the dynamics of metabolic indicators, including protein, carbohydrate and lipid metabolism. Monitoring studies of the biochemical status of vaccinated cows have production and practical significance for the timely detection of metabolic disorders, their correction and maintenance of productive health. As is known, homeostatic regulation of metabolism changes significantly throughout the entire period of pregnancy and depends on the influence of the endocrine system, which regulates the metabolism of proteins, carbohydrates and lipids, ensuring the distribution of nutrients. According to the results of examination of control and experimental animals, although no changes were observed in the control group, in the experimental group the indicators in the blood of some biochemical indicators included in the composition of metabolic products changed. The reason for this is a temporary increase in biochemical indicators in the blood serum of animals after vaccination against foot-and-mouth disease, which is associated with the active functioning of immune cells in the body and the formation of an immune response. Thus, it was found that changes in the biochemical indicators of cattle after vaccination were short-term and did not have a significant effect on the body. Our studies emphasize the importance of an integrated approach to assessing the impact of vaccination on animal metabolism and the need for further research in this area.